Cinema of Actuality : Japanese Avant-Garde Filmmaking in the Season of Image Politics - Furuhata, Yuriko, 1973- (Book collections on Project MUSE., 2013)
Cinema of Actuality analyzes Japanese avant-garde filmmakers' struggle to radicalize cinema in light of the intensifying politics of spectacle and a rapidly changing media environment, one that was increasingly dominated by television.